2018
DOI: 10.15252/embj.201798694
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 is a negative regulator of Mycobacterium tuberculosis phagosome maturation in macrophages

Abstract: Mutations in the leucine‐rich repeat kinase 2 (LRRK2) are associated with Parkinson's disease, chronic inflammation and mycobacterial infections. Although there is evidence supporting the idea that LRRK2 has an immune function, the cellular function of this kinase is still largely unknown. By using genetic, pharmacological and proteomics approaches, we show that LRRK2 kinase activity negatively regulates phagosome maturation via the recruitment of the Class III phosphatidylinositol‐3 kinase complex and Rubicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
134
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 73 publications
11
134
1
Order By: Relevance
“…Recent data imply that distinct pathways regulate uptake kinetics of different particles as well as phagosome functions in macrophages, and these are further controlled by macrophage activation. It was demonstrated that both the phagocytic receptors (Dill et al , ; Balce et al , ) and pro‐inflammatory (Yates et al , ; Trost et al , ; Ghigo et al , ) and anti‐inflammatory activation (Varin et al , ; Balce et al , ) of macrophages affect phagosome functions and these are regulated by signalling pathways such as kinases (Hartlova et al , ) and E3 ligases (O. Bilkei‐Gorzo, T. Heunis, A. Härtlova, M. Trost, unpublished data ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data imply that distinct pathways regulate uptake kinetics of different particles as well as phagosome functions in macrophages, and these are further controlled by macrophage activation. It was demonstrated that both the phagocytic receptors (Dill et al , ; Balce et al , ) and pro‐inflammatory (Yates et al , ; Trost et al , ; Ghigo et al , ) and anti‐inflammatory activation (Varin et al , ; Balce et al , ) of macrophages affect phagosome functions and these are regulated by signalling pathways such as kinases (Hartlova et al , ) and E3 ligases (O. Bilkei‐Gorzo, T. Heunis, A. Härtlova, M. Trost, unpublished data ).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether phagosome-associated cell signalling is independent of its role in cargo degradation has not been well understood. Supporting this notion, recent proteomic studies demonstrated that phagosomes are dynamic organelles that change their composition and function in response to infection or inflammation (Trost et al, 2009;Boulais et al, 2010;Dill et al, 2015;Guo et al, 2015;Naujoks et al, 2016;Hartlova et al, 2018). While the regulation of phagosomal maturation in so-called M1 inflammatory macrophages has been extensively studied, the mechanisms facilitating phagosomal maturation in macrophages involved in tissue repair remain poorly understood (Balce et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…LRRK2 variants are also associated with autoimmune disorders (Witoelar et al, 2017), particularly Crohn's Disease, and with infectious diseases, notably Mycobacterium leprae (Wang et al, 2015;Zhang et al, 2009). LRRK2 expression has also been linked with Mycobacterium tuberculosis infection (Härtlova et al, 2018;Wang et al, 2018). LRRK2 is expressed in a variety of cell lineages, including several immune subsets, notably B cells, neutrophils, monocytes, macrophages and microglia (Atashrazm et al, 2018;Fan et al, 2018;Gardet et al, 2010;Hakimi et al, 2011;Kim et al, 2012;Marker et al, 2012;Moehle et al, 2012;Thévenet et al, 2011) (reviewed in (Lee et al, 2017)).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this notion, recent proteomic studies demonstrated that phagosomes are dynamic organelles that change their composition and function in response to infection or inflammation (Boulais et al, 2010, Hartlova et al, 2018, Naujoks et al, 2016, Trost 85 et al, 2009. While the regulation of phagosomal maturation in so-called M1 inflammatory macrophages has been extensively studied, the mechanisms facilitating phagosomal maturation in macrophages involved in tissue repair remains poorly understood (Balce DR., Keizer.…”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/382853 doi: bioRxiv preprint first posted online Aug. 1, 2018;, Trost et al, 2009, Yates et al, 2007 and anti-inflammatory activation (Balce et al, 2011, Varin et al, 2010 of macrophages affects phagosome functions and these are regulated by signalling pathways such as kinases (Hartlova et al, 2018) and E3-335…”
mentioning
confidence: 99%